Aplikasi Gamifikasi Penilaian Pengetahuan Subjek Sains Tahun 2 Sekolah Rendah Mengenai Tumbuh-tumbuhan, Haiwan dan Manusia - Md Yasin, Mohd Suhaimi; Os Nortika, Os Asri Fikri; Ahmad Shukri, Nur Batrisyia Afrina; Muhammad Aznor, Nurul Najihah (Multidisciplinary Applied Research and Innovation, 2022)
Game-based learning is where we will use the features and principles of games in learning activities. Such learning activities can encourage student engagement and motivation to learn. This game-based learning can be practiced using the app by answering the questions provided. "Science Activity Application for Year 2 Students" can help year 2 students to learn science subjects with more fun. In addition, students can do the activities provided to find out their level of understanding. The study also aims to produce an easy -to -use application. To implement this project, we chose to use Adobe Animate as our main software. The methodology used in our study is to start with the process of data collection, create an application design, and launch our project to find out the effectiveness of the application. In conclusion, it is hoped that this project can run smoothly and achieve the objectives that have been stated. With this application, it is hoped that the exposure to this game -based learning can be used as well as possible.